Full central neurokinin-1 receptor blockade is required for efficacy in depression: evidence from orvepitant clinical studies. (May 2013) - Ratti, Emiliangelo; Bettica, Paolo; Alexander, Robert; Archer, Graeme; Carpenter, David; Evoniuk, Gary; Gomeni, Roberto; Lawson, Erica; Lopez, Monica; Millns, Helen; Rabiner, Eugenii A; Trist, David; et al.
Full, persistent blockade of central neurokinin-1 (NK1) receptors may be a potential antidepressant mechanism. The selective NK1 antagonist orvepitant (GW823296) was used to test this hypothesis. A preliminary positron emission tomography study in eight male volunteers drove dose selection for two randomized six week studies in patients with major depressive disorder (MDD). Displacement of central [ 11 C]GR205171 binding indicated that oral orvepitant doses of 30–60 mg/day provided >99% receptor occupancy for ≥24 h. Studies 733 and 833 randomized patients with MDD and 17-item Hamilton Depression Rating Scale (HAM-D)≥22 to double-blind treatment with orvepitant 30 mg/day, orvepitant 60 mg/day or placebo (1:1:1). Primary outcome measure was change from baseline in 17-item HAM-D total score at Week 6 analyzed using mixed models repeated measures. Study 733 ( n =328) demonstrated efficacy on the primary endpoint (estimated drug-placebo differences of 30 mg: −2.41, 95% confidence interval (CI) (−4.50 to −0.31) p =0.0245; 60 mg: –2.86, 95% CI (−4.97 to −0.75) p =0.0082). Study 833 ( n =345) did not show significance (estimated drug-placebo differences of 30 mg: −1.67, 95% CI (−3.73 to 0.39) p =0.1122; 60 mg: −0.76, 95% CI (−2.85 to 1.32) p =0.4713). The results support the hypothesis that full, long lasting blockade of central NK1 receptors may be an efficacious mechanism for the treatment of MDD.